Navegando pelas ondas do desenvolvimento: Baixada Santista em busca de um porto seguro - desenvolvimento, metropolização e os (des) compassos da gestão urbano-regional em múltiplos olhares sociais - Viana, Mônica Antonia (2010)
This paper is a reflection on the phenomenon of urban metropolization of contemporary cities in the context of the capitalist mode of production, especially at the current stage, facing the impacts of economic globalization and restructuring of productive capital. Thus, it has been sought to critically examine the different dimensions, (inter) connections and contradictions existing among Development, Metropolitanization and Planning, as well as Management of the urban-regional space, in light of the reality of the Brazilian metropolises. Therefore, the phenomenon of the metropolization has been analyzed as a social process, having the objective of empirical investigation the metropolitan area of Baixada Santista (RMBS), in the state of Sao Paulo. In the context of this region, it is sought to explicit the contradictions and conflicts between different social, economic and political forces, which interact and compete in this game of power related to production, reproduction and consumption of the metropolitan urban space. A set of interviews have been used as references, representing the different forces. Metropolization has also been analyzed as a tool of management and control (regionalization plans), through state action and public policies and instruments of planning and management of Brazilian metropolitan regions. Thus, an analysis of the planning system and management of RMBS has been done, which has the function to solve the problem of common interest and promote integrated and sustainable development of the region. The ups and downs have also been evaluated between planning and management of urbanregional space, as well as the inefficacy of urban planning and metropolitan management. Through the exercise of democratic participation, this will set a fragile and incipient regional governance. Concerning the theoretical methodology of the survey, the central point is the analysis of Baixada Santista development, starting from the multiple perspectives of social agents who represent the region, as well as through the interpretation of several interviews carried out by the researcher that permeate the analytical construction of the thesis as a whole